(untitled) (Tzintzun, Revista de Estudios Históricos, 2016)
Against the common opinion that it was the Spanish Crown and its advisors the ones that named the clergy, the article examines the fact that this was not the monarch’s job, but on the contrary, it was the result of a very intricate process of selection in which the Consejo de Indias, the Viceroy, the archbishops of the Cathedral Chapter participated making the decision. This way, when there were three candidates, as in the contest of the canonship, one of them was pointed by the synod examiner and the monarch usually chose him. However, the process had a fundamental aspect: with a well paid, careful and diligent management, there was a great possibility to obtain the benefice (canonry). This way rich families or powerful clergymen related to wealthy corporations could access the position.